ORIENTATION OF ENTREPRENEURS AND BUSINESS PERFORMANCE OF MSME IN PANDEGLANG DISTRICT, PANDEGLANG REGENCY - Yoyoh Guritno; Renny Husniati (Journal of Management and Leadership, 2020)
MSME (Micro, Small, Medium Enterprises) has an important role in the business activities of an area. For this reason, it is necessary to know the general condition of MSMEs and it is also necessary to know whether entrepreneurial orientation influences MSME business performance in Pandeglang District, Pandeglang Regency. Many factors affect MSME business performance including the Entrepreneurial Orientation (EO), with specific dimensions of entrepreneurial orientation over three dimensions, namely, innovativeness, proactiveness, and risk-taking ability and how it affects the performance of MSMEs. This research is targeted to be able to identify the general condition of MSME. Entrepreneurial orientation influences MSME business performance in Pandeglang district Pandeglang regency, Banten Province. The results of the research are expected to be useful for the relevant department in assisting and fostering MSMEs as well as providing an overview for MSMEs actors in improving their business performance.